Ethanol Production from Sweet Sorghum Juice Under Very High Gravity Fermentation by Saccharomyces cerevisiae : Aeration Strategy and Its Effect on Yeast Intracellular Composition - Pattana Laopaiboon (Science Faculty of Chiang Mai University, 2019)
A new technique of aeration during ethanol fermentation from sweet sorghum juice under very high gravity (VHG) condition was investigated to improve ethanol production efficiency of Saccharomyces cerevisiae NP01. Response surface methodology (RSM) analysis showed that the optimal aeration conditions for ethanol production were an aeration rate, aeration time and agitation rate at 2.50 vvm, 4.44 h and 197 rpm, respectively. When the verification experiment under the optimal conditions was performed in a 5-L bioreactor, ethanol concentration (P), productivity (Qp) and ethanol yield (Yp/s) were 131.75 ± 0.76 g l-1, 2.53 ± 0.01 g l-1 h-1 and 0.00 ± 0.76, respectively. Under an unaerated condition (control treatment), the P, Qp and Yp/s values were 120.72 ± 1.37 g l-1, 2.24 ± 0.03 g l-1h-1 and 0.50 ± 0.00, respectively. Additionally, total fatty acids (TFAs) and ergosterol concentrations in the yeast cells at the fermentation time under the optimal aeration conditions were 2637.14 ± 64.39 and 282.37 ± 18.46 µg gDCW-1, respectively. These values under the control conditions were 1587.05 ± 25.33 and 201.09 ± 24.33 µg gDCW-1, respectively. The results clearly indicated that optimal aeration can improve ethanol production efficiency of yeast cells, which might be related to an increase in their intracellular components, i.e., TFAs and ergosterol.